Red recombination enables a wide variety of markerless manipulation of porcine epidemic diarrhea virus genome to generate recombinant virus - Pan, Shuonan; Mou, Chunxiao; Chen, Zhenhai (Frontiers in Cellular and Infection Microbiology, 2024)
Porcine epidemic diarrhea virus (PEDV) is a member of the genera Alphacoronavirus that has been associated with acute watery diarrhea and vomiting in swine. Unfortunately, no effective vaccines and antiviral drugs for PEDV are currently available. Reverse genetics systems are crucial tools for these researches. Here, a PEDV full-length cDNA clone was constructed.Furtherly, three PEDV reporter virus plasmids containing red fluorescent protein (RFP), Nano luciferase (Nluc), or green fluorescence protein (GFP) were generated using Red recombination with the GS1783 E. coli strain. These reporter-expressing recombinant (r) PEDVs showed similar growth properties to the rPEDV, and the foreign genes were stable to culture up to P9 in Vero cells. Using the Nluc-expressing rPEDV, the replication of PEDV was easily quantified, and a platform for rapid anti-PEDV drug screening was constructed. Among the three drugs, Bergenin, Umifenovir hydrochloride (Arbidol), and Ganoderma lucidum triterpenoids (GLTs), we found that GLTs inhibited PEDV replication mainly after the stage of virus "Entry". Overall, this study will broaden insight into the method for manipulating the PEDV genome and provide a powerful tool for screening anti-PEDV agents.